EARLY DETECTION OF BREAST CANCER BY SCREENING MAMMOGRAPHY - MUTTARAK, Malai; CHALOEYKITTI, Ladda; TRAKULTIVAKORN, Hongsin; WANAPIRAK, Chanane; CHAIWUN, Benjaporn; RANGDAENG, Samreung (The ASEAN Journal of Radiology, 2023)
Mammography is currently the best modality for breast cancer screening. We have been performing a mammography screening over the last 3’2 years on 1000 women seen during this period. We detected 3 cancers, all of which were ductal carcinoma-insitu with microinvasion and no axillary node involvement. The overall cancer detection rate was three per thousand. All of our cases were younger than 49 years of age. Our cancer detection rate and stage of detected cancer meet the standard suggested by international reports. Further study to increase our sample size is on-going.